The improvement of solfege singing skills (do, re and mi) for year three pupils by using Kodaly approached / Haslinda Baharudin - Baharudin, Haslinda (2015)
This research was conducted to overcome problems of respondents who cannot sing the solfege pitch do, re and mi accurately. The study sample consisted of eight respondents from Year 3 Jujur identified as having problems to sing the solfege pitches do, re and mi correctly. Preliminary review founds that by conducting pre test and observation, the level of pupils' ability to sing the solfege pitch (do, re and mi) can be identified. After preliminary review founds that five respondent are very weak in mastering the solfege singing do, re and mi pitch, two respondents are weak and only one respondent was considered average. In line with that, this research focused on how to overcome the respondents’ problems to sing the correct pitch by using Kodaly method. A few sectional rhythm patterns and Kodaly hand signs chart were used in interpretation. During teaching and learning been conducted, unstructured observation has been made based on respondents interest, understanding and pupils’ proficiency towards the techniques been used to improve' solfege pitch do, re and mi singing. Pre and post-test were conducted to make a comparison of the effectiveness before and after using the technique. We can see the increment of singing quality among respondents after the Kodaly method had been used.